DOSIMETRY OF IONIZING RADIATION IN SWAMP RICE FARM IN EKOI UBOM AND EKOI IKOT NYOHO, INI LOCAL GOVERNMENT AREA - Atat, Joseph; Ekpo, Sunday; Akankpo A. O.,; Akpan, V. E.,; Essien, I. E., (IJRDO-Journal of Applied Science, 2020)
An assessment of absorbed surface dose rate of ionization radiation in swamp rice field in Ekoi Ubom and Ekoi Ikot Nyoho Ini Local Government Area, Akwa Ibom State, Nigeria was carried out with the aid of diligert survey meter with serial number 60030. We have noted the latitude and longitude as well as the elevation of 11 locations (LT1 to LT11) in Ini using the Global Positioning System (GPS). Contour maps have been generated using Surfer 16 software for easy interpretation. The result of highest annual equivalent dose rate computed is in LT4 with ionizing radiation level of 0.52596µSv/yr. The mean of all locations annual average equivalent dose rate amount to (0.242260 ± 0.035064)µSv/yr. This value is not close to the maximum permissible dosage of 1mSv/yr and 20mSv/yr for the general public and occupational workers (farmers) in the study area respectively, meaning that the study area is not hazardous as far as nuclear radiation is concerned.